STUDENTS' SKILLS IN DIGITAL LITERATURE USING COMIC PAGE CREATOR TO REALIZE PANCASILA STUDENT PROFILE - Martin Indah (Universitas Trunojoyo Madura, 2021)
The purpose of this study was to determine the extent to which digital literacy skills possessed by 5th grade students of SDN 2 Kedungrejo in thematic learning (Indonesian subjects with KD. 3.5 and 4.5) to realize the profile of Pancasila students by using a comic page creator. The steps used in solving this problem is to use descriptive research methods. The implementation of this research was carried out with the subject of 5th grade students of SD Negeri 2 Kedungrejo Kec. Kab. Lamongan consisting of 13 students with details of 5 male students and 8 female students. This activity lasts for 1 month in September 2021. The standard content of Indonesian subjects at the elementary level states that one of the objectives is for students to be able to convey their ideas and knowledge both orally and in writing . Literacy skills to realize the Pancasila student profile when associated with the objectives of these subjects can be summarized by the statement that digital literacy skills are Indonesian language skills by utilizing digital devices as a communication tool to convey ideas and knowledge in order to have global competence and behave according to Pancasila values. The use of the comic page creator application that can be accessed via a smartphone or gadget is one of the efforts as a form of teacher innovation in learning to develop student literacy skills through digital literacy activities to create a Pancasila student profile.